The TRENDadvisor guide to breakthrough profits : - Dukas, Chuck (John Wiley & Sons, 2006)
Whether you're a seasoned professional trader or newcomer to the world of investing, you must develop a defined methodology and consistently apply it to control risk, preserve capital, and harvest profits. Now, The TRENDadvisor Guide to Breakthrough Profits outlines an integrated approach to market analysis and a sound trading strategy, known as the TRENDadvisor Diamond Methodology, this book will assist traders and investors locate low-risk/high-reward trading opportunities